Depending the Total Quality Management Philosophy To Develop Lean Manufacturing Systems: Case Study In the General Company for Heavy Engineering Equipments - الرحيم, اياد محمود; سلمان, ريام غازي (Journal of Economics and Administrative Sciences, 2017)
The continued acceleration in the business environment has led to the need for organizations great attention to quality applied in organizations to meet the needs of customers and stay in the market for as long as possible.Search launched from the underlying problem is the presence of concentrations of defects and waste plaguing the company and to achieve the goal of the study detects the level of quality applied in the factory vessels and reservoirs of the General Company for Heavy Engineering Equipment, As well as calculate wastage rates occurring in the production process and find a relationship between the level of quality and ratios defective in each type of waste, it has been used quantitative measures to measure the level of application of each of (quality, defective, waste resulting from production activities ,waste resulting from re-work, growling resulting from unexpected shutdowns, waste resulting from non-productive activities, and waste resulting from the workers), And finding the relationship and impact between the level of quality and ratios defective for each type of waste for the purpose of testing hypotheses using statistical software (SPSS V.19). Since the results of the study showed that the company is working to maintain the quality of its products and production according to the specifications required only if there waste in the production process It caused a loss to the company in some cases and increase costs in addition to the company's failure to exploit all available energies as the production rate has not exceed 30% of actual capacity.